2015
DOI: 10.1126/science.aaa5458
|View full text |Cite
|
Sign up to set email alerts
|

Titin mutations in iPS cells define sarcomere insufficiency as a cause of dilated cardiomyopathy

Abstract: Human mutations that truncate the massive sarcomere protein titin (TTNtv) are the most common genetic cause for dilated cardiomyopathy (DCM), a major cause of heart failure and premature death. Here we show that cardiac microtissues engineered from human induced pluripotent stem (iPS) cells are a powerful system for evaluating the pathogenicity of titin gene variants. We found that certain missense mutations, like TTNtv, diminish contractile performance and are pathogenic. By combining functional analyses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
557
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 526 publications
(591 citation statements)
references
References 36 publications
29
557
2
3
Order By: Relevance
“…2A,B). Consistent with this finding, a recent study showed a strong correlation between 'percentage spliced in' of nonsense mutation-containing exons and DCM severity (Roberts et al, 2015), and another study using engineered induced pluripotent stem cells suggested that nonsense mutations in exons of TTN with higher levels of percentage spliced in can cause significant contractile deficits via haploinsufficiency of full-length TTN (Hinson et al, 2015). Our generation of a near-null ttn mutant allele by targeting highly used exons in ttn.2 and ttn.1 gives more supporting evidence that exon usage is the underlying mechanism (Fig.…”
Section: Exon-dependent Phenotypes Of Ttn and Their Underlying Mechansupporting
confidence: 65%
See 1 more Smart Citation
“…2A,B). Consistent with this finding, a recent study showed a strong correlation between 'percentage spliced in' of nonsense mutation-containing exons and DCM severity (Roberts et al, 2015), and another study using engineered induced pluripotent stem cells suggested that nonsense mutations in exons of TTN with higher levels of percentage spliced in can cause significant contractile deficits via haploinsufficiency of full-length TTN (Hinson et al, 2015). Our generation of a near-null ttn mutant allele by targeting highly used exons in ttn.2 and ttn.1 gives more supporting evidence that exon usage is the underlying mechanism (Fig.…”
Section: Exon-dependent Phenotypes Of Ttn and Their Underlying Mechansupporting
confidence: 65%
“…Truncated TTN protein was not detected in samples of skeletal muscle (Gerull et al, 2006) or left ventricles (Roberts et al, 2015) from patients with cardiomyopathy. A recent study using engineered induced pluripotent stem cell-derived cardiomyocytes mimicking different A-band truncation mutations from human patients reported a smaller TTN fragment in only one of the three cell lines (Hinson et al, 2015). In contrast, truncated TTN was found in skeletal muscle biopsy specimens from patients with DCM (Gerull et al, 2002) and in a mouse model (Gramlich et al, 2009).…”
Section: Exon-dependent Phenotypes Of Ttn and Their Underlying Mechanmentioning
confidence: 99%
“…Indeed, using constrained microtissues, Hinson and colleagues have demonstrated that human iPSCs with certain missense mutations in titin, a structural sarcomere protein, result in impaired contractility (Fig. 2D,E) and responses to β-adrenergic stress that are similar to those in individuals that develop dilated cardiomyopathy owing to truncated titin variants (Hinson et al, 2015). Moreover, highly aligned microtissues with human pluripotent-stem-cell-derived cardiomyocytes have enabled the development of a tachycardic model of arrhythmogenesis, an aspect of cardiophysiology that has not been previously recapitulated in other microtissue models (Thavandiran et al, 2013).…”
Section: Implementation Of Mechanically Constrained Microtissues Withmentioning
confidence: 99%
“…As additional levels of complexity, the advent of protocols to generate patient-specific CMs suggests that this platform could be used for personalized medicine applications, as well as for mutation-or disease-specific evaluations [29]. Also, by integrating vasculature models into the ECTs, such as the recent AngioChip (Figure 1(j-m)) [20], a circulatory system could be generated to investigate drug delivery methods as well as the effect of the endothelium.…”
Section: Expert Opinionmentioning
confidence: 99%